FABRIKASI KACA FLUORINE DOPED-TIN OXIDE (FTO) MENGGUNAKAN TEKNIK SPRAY PYROLYSIS - Wahyuni, Eka; Darsikin, Darsikin; Saehana, Sahrul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This study aims to determine the results obtained from the fabrication of Fluorine Doped-Tin Oxide (FTO) glass using the Spray Pyrolysis technique. This research is experimental-laboratory. The method used in the manufacture of FTO glass is the spray pyrolysis method to deposit ordinary glass as conductive and transparent FTO glass. The tools and materials used in this research are the OMRON NE-C28 Nebulizer, Digital Ultrasonic Cleaner, Digital Balance, Magnetic Stirrer, Heating Plate (Thermo Scientific Hot Plate), Aluminum Foil, Hoses and Funnels, Statives and Clamps, Glass Substrate, Tin (II) Chloride Dihydrate (SnCl2.2H2O), Ammonium Fluoride (NH4F), Ethanol 96%. The results of the research that have been carried out show that the Ultrasonic Nebulizer is recommended as a tool for making Fluorine-doped Tin Oxide (FTO) thin films on a laboratory scale. The test results of microscopic properties (SEM and XRD), electrical properties (Current and Voltage), and resistance showed that the distance of the spray nozzle to the substrate affects the resistance value of the sample being tested. The closer the distance is given, the thickness of the thin layer increases, so that the electrical resistance decreases. However, a layer that is too thick affects the transparency of the glass. So there must be a balance between electrical resistance and transparency. The results of the optimal transparent conductive glass fabrication in this study were obtained at a distance of 11.5 cm with a temperature of 4500C in 50 minutes, which is 1286.8 Ω.